PERANAN BANK INDONESIA SUMATERA BARAT DALAM PENGEMBANGAN PRODUK UMKM MENGHADAPI MASYARAKAT EKONOMI ASIA 2016 - Tri Irfa Indrayani Nazaruddin (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2016)
The focus of this study to determine the development of UMKM products inencountering the West Sumatran market in 2016. Asia Economic Community studiedaspect is product quality and product branding UMKM in UMKM developmentfunctions of Bank Indonesia. The studies carried out November 2015 - February 2016..With qualitative research methods. The results showed that the function of BankIndonesia UMKM development program has been implemented in accordance with thedevelopment of UMKM products. In 2014, 18 out of 20 UMKM (90%) target BankIndonesia has been able to improve product quality, increase profitability, opening newmarkets as well as more innovation, but if in view of the quantitative that UMKM WestSumatra 501. 410 BPS data, the Department of Cooperatives and UMKM Sumatra west(2015) shows the facilitation of 1.5% (7548) has not been optimal, temporary assistancefrom Bank Indonesia, 0.004% Sumaterra west has not been represented, so manyproducts can not increase the ability of UMKM to improve product quality, branding,capital and markets. Based on the research results suggested the Bank Indonesia theirbodies / organizations standardize UMKM products, as well as provide coachingkonfrehensif making UMKM more competitive on the Asian market economiccommunity.Keywords : Product Quality, Branding Quality, UMKM